2016
DOI: 10.1152/ajpendo.00539.2015
|View full text |Cite
|
Sign up to set email alerts
|

Na,K-ATPase regulation in skeletal muscle

Abstract: Skeletal muscle contains one of the largest and the most dynamic pools of Na,K-ATPase (NKA) in the body. Under resting conditions, NKA in skeletal muscle operates at only a fraction of maximal pumping capacity, but it can be markedly activated when demands for ion transport increase, such as during exercise or following food intake. Given the size, capacity, and dynamic range of the NKA pool in skeletal muscle, its tight regulation is essential to maintain whole body homeostasis as well as muscle function. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 367 publications
(792 reference statements)
1
95
0
3
Order By: Relevance
“…The finding here of a similar increase in the repriming period with GP inhibition or glycogen removal in combination with partial t‐system depolarization clearly demonstrates the importance of glycogenolytically derived ATP for Na + ,K + ‐ATPase activity. In depolarized muscle fibres, Na + ,K + ‐ATPase energy demand is expected to be high (Clausen, ; Pirkmajer & Chibalin, ), further stressing the importance of readily available ATP production for the Na + ,K + ‐ATPases. In support of this, Dutka and Lamb () found that stimulation of glycolytic ATP production by the addition of phosphoenolpyruvate decreases the repriming period in partly depolarized, but not well‐polarized, fibres (Dutka & Lamb, ).…”
Section: Discussionmentioning
confidence: 99%
“…The finding here of a similar increase in the repriming period with GP inhibition or glycogen removal in combination with partial t‐system depolarization clearly demonstrates the importance of glycogenolytically derived ATP for Na + ,K + ‐ATPase activity. In depolarized muscle fibres, Na + ,K + ‐ATPase energy demand is expected to be high (Clausen, ; Pirkmajer & Chibalin, ), further stressing the importance of readily available ATP production for the Na + ,K + ‐ATPases. In support of this, Dutka and Lamb () found that stimulation of glycolytic ATP production by the addition of phosphoenolpyruvate decreases the repriming period in partly depolarized, but not well‐polarized, fibres (Dutka & Lamb, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the repolarization phase of the skeletal muscle action potential, K + exits the myoplasm via delayed rectifier K + channels to restricted extracellular compartments before being returned actively to the fiber by the Na + /K + -ATPase (31) or passively via inward rectifier K + channels when the membrane potential becomes more negative than E K (32)(33)(34)(35). During LFS, these clearance mechanisms are sufficient to maintain the K + gradient (31). However, transport by the pump and inward rectifier channels cannot keep pace with the K + efflux via delayed rectifier channels during prolonged depolarization or HFS protocols similar to those employed by Lee and colleagues (15,30,[33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…, ; Tang et al . ; Pirkmajer & Chibalin, ). Expression of tetrapod FXYD4 is regulated by aldosterone (Capurro et al .…”
Section: Discussionmentioning
confidence: 99%
“…FXYDs in fishes and mammals are regulated by hormones (Despa et al 2005;Tipsmark et al 2010Tipsmark et al , 2011Tang et al 2012;Pirkmajer & Chibalin, 2016). Expression of tetrapod FXYD4 is regulated by aldosterone (Capurro et al 1997;Brennan & Fuller, 1999;Shi et al 2001), a major mineralocorticoid in terrestrial vertebrates (Rossier et al 2015).…”
Section: Functional Perspectives Of Early Diversification Of Small Trmentioning
confidence: 99%